Impacto de los efectos lineales y no lineales en sistemas WDM-PON con formato de modulación DPSK (2015)
In this paper we analyze the impact in the requirements of the linewidth of the laser, due to the linear and non-linear effects introduced by the optical fiber, in a WDM-PON transmission system using DPSK modulation format. We measured the BER for different data bit rates, transmitted power and dispersion coefficient of the optical fiber. The study was performed using simulations in the computational tool OPTSIM. We found that if the data bit rate is increased, it is possible to use optical sources with higher linewidth using DPSK modulation format, decreasing the cost of the transmitter. Additionally, we proved that the non-linear effects mostly affect the transmission systems where optical fibers with dispersion coefficients near zero are used.